Combining viscosity-restricted intramolecular motion and mitochondrial targeting leads to selective tumor visualization. Issue 49 (15th May 2020) - Yu, Le; Zhang, Jun Feng; Li, Mingle; Jiang, Dewei; Zhou, Ying; Verwilst, Peter; Kim, Jong Seung
Abstract : We report a novel fluorescent molecular conjugate, V-M1, enabling an accurate visualization of tumor tissues. Abstract : We report a novel fluorescent molecular conjugate, V-M1, enabling an accurate visualization of tumor tissues. The emission wavelength of V-M1 exceeds 650 nm, which is well within the near-infrared therapeutic window. Tumor accumulation of this cationic dye allows the visualization of cancerous cells as a function of mitochondrial viscosity.